Semantic mining in clusters from signaling pathways networks - Aguilar Castro, J. (2015)
This paper describes how to semantically enrich clusters from signaling pathways networks. The study is divided into two phases, the first is the detection of clusters in signaling pathways networks, after getting these clusters, they are passed to an extraction process of centrality within each one, so the second phase can enrich them semantically. The centrality chosen for the case study is the measure of closeness to other nodes, and it is who is enriched semantically in each cluster. The selected case study is the signaling pathway of TGF-?, and the central nodes found were enriched with the Gene Ontology. © 2015 IEEE.